A comprehensive review of denosumab for bone metastasis in patients with solid tumors. (2nd January 2016) - Gül, Gözde; Sendur, Mehmet A.N.; Aksoy, Sercan; Sever, Ali R.; Altundag, Kadri
Abstract: Background: Denosumab is fully human monoclonal antibody that specifically binds and inactivates receptor activator of NF-kB ligand (RANKL), an important ligand that regulates bone remodeling. In this review, we aimed to show the clinical data about denosumab treatment and discuss its advantages for the management of patients with solid tumors and bone metastasis. Scope: Denosumab showed positive results in clinical studies of solid tumors with bone metastasis. PubMed database and ASCO Symposium Meeting abstracts were searched until August 2015 by using the terms 'denosumab', 'RANKL inhibitor' and 'bone metastasis'. The last search was on 21 August 2015. All resulting studies were retrieved and were also checked for related publications. Clinical trials in this review fulfilled the following criterion: inclusion of sufficient data to allow estimation of the efficacy and safety of denosumab. Findings: The effects of denosumab on skeletal-related events (SREs) were investigated in three large randomized trials: one in patients with breast cancer, one in patients with prostate cancer, and one in patients with multiple myeloma or solid tumors other than breast or prostate cancer. In the breast cancer and prostate cancer studies denosumab was non-inferior and also superior to zoledronic acid in terms of the primary outcome time to first on-study SRE. In the third study denosumab was non-inferior to zoledronic acid but was not superior to zoledronic acid in solid tumors excluding breast and prostate cancer with bone metastases. In the three studies median overall survival and disease progression rates were similar between zoledronic acid and denosumab. Denosumab has also been studied in bone loss associated with hormonal therapy in both breast and prostate cancer. Adjuvant denosumab significantly reduced the risk of clinical fracture risk by 50% in breast cancer patients and by 62% in non-metastatic prostate cancer patients treated with adjuvant aromatase inhibitors or androgen deprivation therapy. In addition, biochemical markers of bone turnover and fractures were significantly reduced in patients under denosumab treatment. Conclusion: The promising outcomes in the initial trials with denosumab have shown clinical activity and a favorable safety profile in patients with solid tumors and bone metastasis. Denosumab significantly reduced treatment-related osteoporosis associated with breast and prostate cancer and was superior to zoledronic acid in prevention or delaying of SRE.